1951
DOI: 10.1021/ac60055a027
|View full text |Cite
|
Sign up to set email alerts
|

Coulometric Determination of Acid

Abstract: m HW l704oC h e m is try -0 a n t r a l THE CQtJLOHETBIC DETERMINATION OF ACID t y V . N. C arson, J r and Roy Ko A n a ly t ic a l S e c tio n T e c h n ic a l S e rv ic e s D iv i8 io n M arch 1 , 1^.0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1953
1953
1972
1972

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The linear relationship between absorbance ratio and quantity of electricity, as expected from the theoretical consideration, proved valid with solutions of uni-univalent electrolytes (sodium chloride and potassium bromide) and uni-bivalent electrolytes (sodium sulfate and calcium chloride) if the solution wras unbuffered (Figure 3). Because, in the extremes of the transformation region of the indicator, Equation (2) does not hold and the smaller absorbance value (A or A') may introduce the greater error in the calculation of the absorbance ratio (A to A'), the available absorbance ratios should be limited within the range from 0.2 to about 1.0. When the solution to be analyzed contains a slightly acid constituent, and consequently a buffer action displays itself in the transformation region of the indicator, the absorbance ratio shows a sluggish decrease, nonlinear to quantity of electricity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The linear relationship between absorbance ratio and quantity of electricity, as expected from the theoretical consideration, proved valid with solutions of uni-univalent electrolytes (sodium chloride and potassium bromide) and uni-bivalent electrolytes (sodium sulfate and calcium chloride) if the solution wras unbuffered (Figure 3). Because, in the extremes of the transformation region of the indicator, Equation (2) does not hold and the smaller absorbance value (A or A') may introduce the greater error in the calculation of the absorbance ratio (A to A'), the available absorbance ratios should be limited within the range from 0.2 to about 1.0. When the solution to be analyzed contains a slightly acid constituent, and consequently a buffer action displays itself in the transformation region of the indicator, the absorbance ratio shows a sluggish decrease, nonlinear to quantity of electricity.…”
Section: Resultsmentioning
confidence: 99%
“…As the striking enhancement of the color obtained with the molybdate reagent and silicate in the presence of TCA suggested that this procedure might be analytically useful, silicate was determined with both the system used for phosphate (1) and the method devised for silicate (2) with TCA present. Also, the concentration of the sulfuric acid was varied to determine the effect of intermediate concentrations.…”
mentioning
confidence: 99%
“…Modern electrometer tubes can measure extremely small currents and potentiometric indication of end points now makes it possible to work with relative ease in the submicrogram range. Examples of such titrations include the coulometric determination of manganese by Cooke, Reilley, and Furman (82); acids by Carson and Ko (29); silver by Lord, O'Neill, and Rogers (108); uranium by Furman, Bricker, and Dilts (60, 61); and vanadium by Furman, Reilley, and Cooke (63). These latter investigators have also pointed out the merits of the coulometric method in cerate titrimetry (62).…”
Section: Titrimetrymentioning
confidence: 99%
“…THE detection of the equivalence point in coulometric titrations has received considerable attention. Both potentiometric (2)(3)(4)6) and amperometric (1, 5, 7, 8, 10, 13, 17) methods have been investigated, and a detailed study of electrometric processes has been published (16). With such methods, the problem of obtaining consistent electrode behavior has arisen, and has occasionally necessitated meticulous care in the handling of the electrodes.…”
mentioning
confidence: 99%